Experimental seismic response of a column-and-tie wooden structure. Issue 8 (June 2019) - Xue, Jianyang; Xu, Dan; Qi, Liangjie
A half-scale model of a two-story and two-span column-and-tie wooden structure was fabricated and tested on the shaking table to assess the seismic behavior of the structure under various base input intensities. The dynamic characteristics, acceleration response, displacement response and shear force distributions were measured and assessed. Besides, the cumulative hysteretic energy dissipation performance of the model was analyzed. The test results revealed that with the increasing magnitude of earthquake excitation, the natural frequency and stiffness of the model structure decreased, and the damping ratio increased. The acceleration amplification factor of each layer fluctuated between 0.286 and 1.383. The wooden house is directly placed on the concrete slab, which to some extent plays a role in sliding isolation. The model dissipates seismic energy mainly by the first layer. When the earthquake excitation was 0.22 g and 0.40 g, the model responded seriously, and the maximum inter-story drifts of the model was 1/65 and 1/35, respectively. When the earthquake input reached 0.5 g, the structure did not collapse. This demonstrates that the wooden structure has strong capability of lateral resistance and deformation resistance. Furthermore, the wooden wallboard component acts as the first seismic line under earthquake excitation, meeting the characteristics of "A wall falls down, while the house will not collapse." This article can help guide the seismic design and performance assessment of traditional wooden constructions.